2010
DOI: 10.2519/jospt.2010.3073
|View full text |Cite
|
Sign up to set email alerts
|

Core Muscle Activation During Swiss Ball and Traditional Abdominal Exercises

Abstract: Rafael f. escamilla, PT, PhD, CSCS, FACSM1 • Clare lewis, PT, PsyD, MPH, MTC, FAAOMPT2 • DunCan Bell, MPT3 Gwen BramBlet, MPT3 • Jason Daffron, MPT3 • steve lamBert, MPT3 • amanDa PeCson, MPT3 roDney imamura, PhD 4 • lonnie Paulos, MD 5 • James r. anDrews, MD 6 Core Muscle Activation During Swiss Ball and Traditional Abdominal Exercises t he "core" has been used to refer to the lumbopelvic-hip complex, which involves deeper muscles, such as the internal oblique, transversus abdominis, transversospinalis (multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
1
33

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(228 citation statements)
references
References 32 publications
8
176
1
33
Order By: Relevance
“…Trunk strengthening should now focus on global musculature in all planes, since deep core activation has previously been established. EMG analysis of trunk musculature has shown that bridging, exercise ball crunches, forward roll outs, prone dips, pikes, and quadruped opposite arm and leg lifts are most effective at activation the trunk and hip extensors [27,35].…”
Section: Sagittal Plane Hip Muscle Requirements For Normal Gaitmentioning
confidence: 99%
See 1 more Smart Citation
“…Trunk strengthening should now focus on global musculature in all planes, since deep core activation has previously been established. EMG analysis of trunk musculature has shown that bridging, exercise ball crunches, forward roll outs, prone dips, pikes, and quadruped opposite arm and leg lifts are most effective at activation the trunk and hip extensors [27,35].…”
Section: Sagittal Plane Hip Muscle Requirements For Normal Gaitmentioning
confidence: 99%
“…Iliopsoas isometrics with simultaneous core activation and trunk extensor activation should also be performed in this position and will help to reestablish the hip flexor and lumbar extensor force couple during open chain hip flexion [19,25]. Global trunk musculature including the oblique externus and internus, rectus abdominus, and erector spinae causes movement of the trunk and controls load transfer from the lower extremities to the pelvis and spine [26,27]. Muscle activation of these groups is also important during this phase to reestablish appropriate load transfer during weight bearing and as the patient becomes more independent with activity of daily living.…”
Section: Early Muscle Activationmentioning
confidence: 99%
“…• shoulder abduction at 90°, internal rotation (seated) [28] • shoulder abduction at 90°, elbow flexed to 90° (seated) [34] • shoulder external rotation and abduction, shoulder abducted to 20°, elbow flexed to 90°, no shoulder flexion [29] infraspinatus • shoulder external rotation, arm at side, elbow flexed to 90° (seated) [28,31,34] • shoulder external rotation, shoulder abducted to 45°, elbow flexed to 90°, no shoulder flexion [29] subscapularis • shoulder internal rotation, arm at side, elbow flexed to 90° (seated) [28,34] • shoulder internal rotation, shoulder abducted to 45°, elbow flexed to 90°, no shoulder flexion [29] latissimus dorsi • shoulder depression with resistance or adduction and internal rotation, arm at side (seated) [28] • shoulder extension and internal rotation with arm straight, abducted to 30° in the coronal plane and internally rotated [29] • shoulder extension (prone lying) [35,36] serratus anterior • scapular protraction, shoulder abducted to 90°-100° (seated) [28] • scapular protraction, elbow flexed to 45°, shoulder abducted to 75° and internally rotated to 45° [29] upper rectus abdominis…”
Section: Maximal Voluntary Isometric Contractionsmentioning
confidence: 99%
“…• trunk flexion, hips and knees flexed to 90°, feet supported, trunk in full flexion (supine) [35,36] • trunk flexion, legs bent at 45°,and secured, trunk position not mentioned (supine) [37] internal oblique • trunk flexion and lateral flexion, hips and knees flexed to 90°, feet supported, trunk in full flexion and rotated contra-laterally (supine) [35] • trunk flexion and lateral flexion, hips and knees flexed to 90°, feet supported, trunk in full flexion and rotated ipsi-laterally (supine) [36] gluteus maximus • hip extension, hip flexed 45° (prone) [38] • back extension, hip flexed 30° (seated) [39] • hip abduction at 10° abduction, leg fully extended (side lying) contra-lateral knee and hip flexed 30° [40] gluteus medius…”
Section: Maximal Voluntary Isometric Contractionsmentioning
confidence: 99%
See 1 more Smart Citation